2005
DOI: 10.1002/bies.20328
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of siRNA‐mediated transcriptional gene silencing

Abstract: The RNAi machinery is not only involved with post-transcriptional degradation of messenger RNAs, but also used for targeting of chromatin changes associated with transcriptional silencing. Two recent papers determine the global patterns of gene expression and chromatin modifications produced by the RNAi machinery in fission yeast.(9, 10) The major sites include the outer centromere repeats, the mating-type locus and subtelomeric regions. By comparison, studies of Arabidopsis heterochromatin also implicate tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the classic model, and similarly as in mammalian cells, plant telomeres were viewed as heterochromatic loci (27). A more recent study, however, characterized A. thaliana telomeric chromatin as an intermediate heterochromatin possessing both hetero- and euchromatin-specific histone modifications (8).…”
Section: Introductionmentioning
confidence: 99%
“…In the classic model, and similarly as in mammalian cells, plant telomeres were viewed as heterochromatic loci (27). A more recent study, however, characterized A. thaliana telomeric chromatin as an intermediate heterochromatin possessing both hetero- and euchromatin-specific histone modifications (8).…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidence has shown that gene silencing is widely adopted in plant immunity. In the past, studies often focused on transposon or siRNA-mediated RNA silence [5,6] . Since miRNAs and siRNAs share many features in common, it is supposed that miRNAs may also be involved in silencing invaders.…”
Section: Introductionmentioning
confidence: 99%
“…Control shRNA contained the same base composition as IE-3 specific RNAs but the base sequence was scrambled. This inhibitory RNA is therefore initially expressed as shRNA but is then processed by the enzyme Dicer into siRNA which is the active component in the RNA induced silencing complex (RISC) [40]. The transfection efficiency of IE-3 specific fluorescently labeled siRNAs or GFP reporter plasmids into the murine bone marrow stromal cell line M2-10B4 was 70-80% (not shown).…”
Section: Resultsmentioning
confidence: 99%